Efektivitas Senam Nifas Terhadap Kelancaran Eliminasi Pada Ibu Nifas di Desa Pamoyanan Kecamatan Kadipaten Kabupaten Tasikmalaya - Nita Nurvita (Jurnal Medika Cendikia, 2016)
The process of health recovery in the puerperium is very important for the mother after giving birth. According to the preeliminary study at Pamoyanan District Kadipaten Tasikmalaya found 62% of postpartum women experience disorder in their elimination pattern. This study aimed to determine the effectiveness of postpartum exercises on the elimination pattern of puerperal mother’s in the Pamoyanan Disctrict Kadipaten Tasikmalaya. The method used quasi-experimental, using praeksperimental design with static group comparison mode. Data colection using primary data by questionnaires. The study population was all post-partum mothers of period March-April 2014, using total sampling found 35 people. The data was prosced by SPSS. Based on survey results, 77,8% good elimination pattern of postpartum women who did do puerperal exercises. While only 22.2% good elimination pattern of postpartum women who did not do puerperal exercises. The results also showed that there was a significant differents with the value = 0.004. Midwives expected to implement maternal puerperal exercise gradually, according to the standar on puerperal exercises.